Longitudinal Association Between Children’s Callous-Unemotional Traits and Social Competence: Child Executive Function and Maternal Warmth as Moderators - Kim, Hyunah; Chang, Hyein (Frontiers in Psychology, 2019)
This study examined the longitudinal association between children’s early callous-unemotional (CU) traits and social competence in the transition to school-age, and tested whether this relationship was moderated by child executive function and maternal warmth. Participants were 643 children (49% girls) who were part of the Panel Study on Korean Children (PSKC) of the Korea Institute of Child Care and Education (KICCE). Mothers rated children’s CU at 5 years and executive function at 8 years, and maternal warmth at 5 years. Teachers reported on children’s social competence at 8 years. Results of the model including child executive function as the moderator indicated that deficits in child executive function and child sex (boys) predicted lower social competence. In addition, the moderating effect of executive function on the relationship between CU and social competence approached a trend such that CU predicted lower social competence only for children with lower executive function. In the model that included maternal warmth as a moderator, CU traits was associated with lower social competence, and this effect was more pronounced for boys as indicated by a significant effects of CU x child sex on social competence. The findings are discussed with respect to considering individual and contextual factors by which early CU becomes associated with individual differences in children’s social competence.